Review of Mott-Schottky-Based Nanoscale Catalysts for Electrochemical Water Splitting - Krishnamachari M.; Lenus S.; Pradeeswari K.; Arun pandian R.; Kumar M.; Chang J.-H.; Muthu S.P.; Perumalsamy R.; Dai Z.; Vijayakumar P. (American Chemical Society, 2024)
Fundamental structural modification of nanomaterials perpetually presents a phenomenal technique to control the electronic structure of active sites, thereby improving the electrocatalytic activities. Nevertheless, appropriate surface reconstruction is necessary to overcome the large electrochemical overpotential that remains unexplored. In such scenarios, a deep understanding of fundamental structural modification mechanisms, including the Janus structure, spillover effect, d-band center shift theory, and interfacial coupling, is essential. One such fundamental interface and valence engineering strategy includes the Mott-Schottky (M-S) effect. Recently, M-S heterostructure catalysts have piqued the interest of researchers due to their ability to enable mass transport, regulate the density of states, enable continuous rapid electron transfer via band bending, and create a synergistic effect at the metal-semiconductor interface. In recent years, there has been a rise in the number of publications related to the M-S effect on electrocatalysis. In this review, we comprehensively summarize the M-S mechanism and the structural advantages of the M-S heterointerface with various nanoscale featured transition metal nitrides, phosphides, carbides, oxides, hydroxides, chalcogenides, and noble metal composites. Finally, we briefly propose the obstacles, limitations, possibilities, and future directions for M-S heterostructure catalysts in water electrolysis. 2023 American Chemical Society.